MAKNA KESATUAN GEREJA DALAM DOA YESUS UT OMNES UNUM SINT (Studi Eksegesis Yohanes 17:21-23) - Jimmy Rungkat (Politeknik Amamapare, 2022)
This study aims to understand the essence of the meaning of the Lord Jesus' Prayer Ut Omnes Unum Sint in John 17:21-23 in order to restore the spirit of the churches in carrying out Missio Dei on this earth. Through the hermeneutic-exegetic study method, it was found that the meaning of the unity of the church as the essence of the Lord Jesus Prayer Ut Omnes Unum Sint is unity in a spiritual sense, namely one in love who is willing to work together and willing to appreciate and learn with the differences of everyone around him without any division. or separation to build each other up and create peace in order to display the work of Christ in it.